23 Outcomes of creating an automated repeat lactate rule in sepsis patients with lactate levels ≥2. (25th November 2019) - Ayad, Mary; Karanth, Siddharth; Narat, Michelle; Luther, Katharine; Patel, Bela
Abstract : Background: Sepsis is a complex disease process that possesses a socioeconomic burden in the U.S. 1 Serum lactate and lactate clearance form an important component of the sepsis resuscitation bundle 2 and high levels correlate with worse outcomes. 3 4 5 Previous studies emphasized the importance of utilizing lactate monitoring to guide resuscitation to improve mortality. 6 7 Objectives: We aimed to enhance lactate monitoring and lactate guided resuscitation in sepsis patients with lactate levels ≥2 mmol/L in order to improve outcomes. Methods: An EMR automated Q2 lactate repeat orders for sepsis patients who have an initial lactate level ≥2 mmol/L was implemented. Lactate dashboards showing all patient-level lactate values during initial resuscitation was incorporated into Hospital Sepsis Committee Multi-Disciplinary meetings. Results: We included 1774 adult sepsis patients admitted from the ED to MICU from October 2014 to September 2018 who had an initial lactate level ≥2 mmol/L. We aimed to compare the median time from ED arrival to lactate reduction to <2 mmol/L, median time from 1st elevated lactate result to lactate <2 mmol/L and the median length of stay (LOS). Post-intervention, the time from ED arrival to lactate <2 mmol/L for those patients with an elevated lactate significantly reduced by 10.56 hours and the time from first elevated lactate to lactate <2 mmol/L significantly reduced by 9.51 hours. LOS reduced by 3 days post intervention. Conclusions: Implementing an automated repeat lactate order for sepsis patients along with a multi-disciplinary review of dashboards resulted in an improvement in lactate clearance and a reduction in LOS. Further studies are needed to investigate this finding.